Study the Impact of the Substrate Temperature on the Optical Properties of Thin Film - Chkuer, Saja Eabd Alamir; Hamadi, Tabark Talib; Fouad Habib, Daha Fareer; Zeboon, Yaqeen Ali; Kazim, Noor Hameed (American Journal of Botany and Bioengineering, 2024)
In the existing work, the optical properties of CdZnO thin films deposited on glass substrates by using pulsed laser deposition (PLD) technique at different substrate temperature RT, 100, 200 and 300C° were measured by UV-VIS spectrophotometer at room temperature in the range from 300 to 1100nm for the potential applications in the new optoelectronic devices. The optical transmission results shows that the transparency of CdZnO films deposited at room temperature is greater than 40%, which increases with increasing substrate temperature to reach to 60% at 300C°. The optical band gap energy was found to be decreased from 3.2 eV to 2.7 eV with increasing substrate temperature. The variation of absorption coefficient and extinction coefficient with wavelength also studied in this work.